Variation of porosity, pore size distribution and soil physical properties under conservation agriculture - GHOSH, TRIDIV; MAITY, PRAGATI PRAMANIK; DAS, T K; KRISHNAN, PRAMEELA; BHATIA, ARTI; BHATTACHARYA, PRIYA; SHARMA, D K (The Indian Journal of Agricultural Sciences, 2020)
For sustainable crop production and maintenance of soil health, conservation agriculture (CA) practices provides an opportunity for improving soil structure and physical health, nutrient and water use efficiency, soil organic carbon and mitigation of greenhouse gases emission from agriculture. CA is primarily based on four crop management practices such as minimum soil disturbance or no-tillage; permanent or semi-permanent retention of crop residue; crop rotation and control traffic. Different CA management practices affect crop yield as well as soil properties. CA makes necessary modifications in different soil hydro-physical properties, viz. increase in soil water infiltration, reduction in water runoff and soil loss, and reduction in evaporation loss. No tillage (NT), residue retention and crop rotation combined effect the soil organic carbon concentration. Different crop rotations and residue retentions and crops with different rooting depths used in CA practices have proved to reduce the compaction constraints.CA can help to mitigate GHG emissions, viz methane (CH4) and nitrous oxide (N2O) from agriculture by improving soil C sequestration, enhancing soil quality, nitrogen and water use efficiencies, and decreasing fuel consumption. But effect of CA and conventional agricultural practices of porosity and pore size distribution is very much limited. When CA is practiced for six to ten years there is improvement in soil structure, porosity and pore size distribution, macro-micro faunal activity, and organic matter content..The soil under ZT has the lowest porosity as compared to conventional management practices. The highest porosity and the maximum connected pores are frequently seen in conventionally tilled soil. In this paper, an attempt has been made to review the variation of porosity and pore size distribution and other soil physical properties under conservation agricultural practices.